Lenalidomide plus Dexamethasone for Relapsed or Refractory Multiple Myeloma - Meletios Α. Dimopoulos; Andrew Spencer; Michael Attal; H. Miles Prince; Jean‐Luc Harousseau; Anna Dmoszyńska; Jesús F. San Miguel; Andrzej Hellmann; Thierry Façon; Robin Foà; Alessandro Corso; Zvenyslava Masliak; et al. (2007)
Lenalidomide is a structural analogue of thalidomide with similar but more potent biologic activity. This phase 3, placebo-controlled trial investigated the efficacy of lenalidomide plus dexamethasone in the treatment of relapsed or refractory multiple myeloma.Of 351 patients who had received at least one previous antimyeloma therapy, 176 were randomly assigned to receive 25 mg of oral lenalidomide and 175 to receive placebo on days 1 to 21 of a 28-day cycle. In addition, all patients received 40 mg of oral dexamethasone on days 1 to 4, 9 to 12, and 17 to 20 for the first four cycles and subsequently, after the fourth cycle, only on days 1 to 4. Patients continued in the study until the occurrence of disease progression or unacceptable toxic effects. The primary end point was time to progression.The time to progression was significantly longer in the patients who received lenalidomide plus dexamethasone (lenalidomide group) than in those who received placebo plus dexamethasone (placebo group) (median, 11.3 months vs. 4.7 months; P<0.001). A complete or partial response occurred in 106 patients in the lenalidomide group (60.2%) and in 42 patients in the placebo group (24.0%, P<0.001), with a complete response in 15.9% and 3.4% of patients, respectively (P<0.001). Overall survival was significantly improved in the lenalidomide group (hazard ratio for death, 0.66; P=0.03). Grade 3 or 4 adverse events that occurred in more than 10% of patients in the lenalidomide group were neutropenia (29.5%, vs. 2.3% in the placebo group), thrombocytopenia (11.4% vs. 5.7%), and venous thromboembolism (11.4% vs. 4.6%).Lenalidomide plus dexamethasone is more effective than high-dose dexamethasone alone in relapsed or refractory multiple myeloma. (ClinicalTrials.gov number, NCT00424047 [ClinicalTrials.gov].).